Competition-based learning and project-based learning to promote undergraduate students’ motivation and performance in mathematics / Tammie Christy Saibin ... [et al.] - Saibin, Tammie Christy; Ung, L. Ling; Janteng, Janvin; Matmali, Norfazillah (Universiti Teknologi MARA, Kedah, 2024)
A combination of two well-known learning models, projectbased learning (PBL) and competition-based learning (CBL) maximises the advantages while avoiding the disadvantages of competition in Mathematics instruction. Thus, this study aims to improve the teaching and learning quality and enhance the learning outcomes of Mathematics instruction. To that end, the research hypotheses investigate the influence of the CBL-PBL approach on students’ learning based on their engagement and educators’ perspectives of the approach. A questionnaire was employed and distributed to 36 students and 2 lecturers who were using and implementing the CBL-PBL approach to achieve the research objectives. Non-parametric statistics tests were used to analyse the results. A significant relationship was found between the CBL-PBL approach and students’ learning outcome based on their learning engagement, collaboration, authentic learning, disciplinary subject learning, and interactiveness. The results suggest that the CBL-PBL approach can maximise the students’ learning outcomes by bridging academic theories and real-world practices through competition. Thus, the CBL-PBL approach is recommended for educational use with proper planning.